The Role of Academic Supervision in Enhancing the Implementation of Social-Emotional Learning Programs in Schools - Arifin, Muhammad Nabil; Saguinsin, Israel (PPSDP International Journal of Education, 2025)
This study aims to explore the role of academic supervision in enhancing the implementation of Social-Emotional Learning (SEL) programs in schools. The research employed a qualitative descriptive method, involving interviews with teachers, principals, and SEL program coordinators at SIS Palembang. Data was also collected through document analysis and classroom observations. The findings indicate that academic supervisors, including headteachers and SEL coordinators, play a crucial role in shaping the success of SEL programs. Headteachers provide vision, support, and resources, while coordinators ensure the smooth implementation and evaluation of the program. Teachers, as the primary implementers, contribute to the program’s effectiveness through their engagement and creativity in delivering SEL activities. The study highlights the importance of collaborative efforts between these stakeholders in creating a supportive environment for SEL, ultimately leading to positive student outcomes. Furthermore, the study underscores the need for ongoing professional development and support for teachers to effectively implement SEL programs.